Digitalisasi Marketing Dalam Mengembangkan Usaha Berbasis Teknologi di Desa Batu Karang Kecamatan Payung Kabupaten Karo - Ikhwah Annisa; Yenti Arsini; Nova Fitri Yasdiana; Ridho Afito; Nurul Jannah (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The development of digital technology has transformed the way businesses market their products and grow their businesses. This study aims to determine how digital marketing plays a role in developing technology-based businesses in Batu Karang Village, Payung District, Karo Regency. The method used was a qualitative approach, using observation and interviews with several business owners who utilize digital media for marketing activities. The results show that most business owners have used social media such as Facebook, Instagram, and WhatsApp Business as promotional tools. The implementation of digital marketing has been proven to help expand market reach and increase sales. However, obstacles such as limited digital skills, lack of training, and suboptimal internet connections remain major obstacles. Therefore, digital marketing plays a crucial role in the development of technology-based businesses, especially when supported by increased digital literacy and adequate infrastructure.